Metal artifact reduction techniques in musculoskeletal CT-imaging. Issue 107 (October 2018) - Wellenberg, R.H.H.; Hakvoort, E.T.; Slump, C.H.; Boomsma, M.F.; Maas, M.; Streekstra, G.J.
Highlights: Metal artifacts impede the value and diagnostic accuracy of CT. Modifying acquisition, reconstruction and visualization parameters reduce artifacts. Combining DECT and MAR software is often but not always the best solution in MAR. MAR techniques provides improved visibility of the bone-metal interfaces. Advances in prosthetic imaging are reinforced by advances in prosthetic design. Abstract: It is known that metal artifacts can be reduced by modifying standard acquisition and reconstruction, by modifying projection data and/or image data and by using virtual monochromatic imaging extracted from dual-energy CT. In this review we focus on the origin of metal artifacts, technical background of commercially available metal artifact reduction (MAR) algorithms and the value of dual-energy CT and MAR software for different metal hardware in current clinical practice. Virtual monochromatic imaging reduces beam-hardening artifacts, where metal artifact reduction software effectively reduces artifacts caused by extensive photon-starvation. Both techniques have their advantages and disadvantages, and the combination of both techniques is often but not always the best solution regarding metal artifact reduction. Advances in prosthetic imaging are reinforced by advances in prosthetic design. Providing implant specific information prior to scanning is important in order to adjust the metal artifact reduction approach, minimize artifacts and optimize image quality and diagnostic value of CT.